1996
DOI: 10.1111/j.1365-2494.1996.tb02063.x
|View full text |Cite
|
Sign up to set email alerts
|

The conservation management of mesotrophic (meadow) grassland in northern England. 1. Effects of grazing, cutting date and fertilizer on the vegetation of a traditionally managed sward

Abstract: The results are reported from an experitneni on the eftecis of culting date (14 June. 21 July and 1 September), tertiiizer appiicalion (none or 80 kg ha' N plus 40 kg h;r' P iind K) and grazing treatments (none, ;iutumn or aurtimn plus spring) on lhe vegetation ol' an upland mesotrophic grassland in UpperTee.sdale. northern England, UK.Ettects on planl species number and cover are reported for 4 years (1989-93) of treatment. Effects on 'species -attribute.s' are given for the fourth year.The ce.ssation of graz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Consistently with this pattern, mineral fertilization led to a significant 12% to 21% reduction in number of plant species in mesotrophic grasslands of northern England (Smith et al, 1996a). Mineral fertilization reduced the cover of relatively stress-tolerant grasses (Anthoxanthum odoratum, C. cristatus) and small-stature Bellis perennis and Plantago lanceolata, whereas benefiting competitive H. lanatus and P. trivialis.…”
Section: Resultssupporting
confidence: 59%
“…Consistently with this pattern, mineral fertilization led to a significant 12% to 21% reduction in number of plant species in mesotrophic grasslands of northern England (Smith et al, 1996a). Mineral fertilization reduced the cover of relatively stress-tolerant grasses (Anthoxanthum odoratum, C. cristatus) and small-stature Bellis perennis and Plantago lanceolata, whereas benefiting competitive H. lanatus and P. trivialis.…”
Section: Resultssupporting
confidence: 59%
“…Most of the published literature is concerned with the effect of single management factors on meadow communities. This does not provide any opportunity to study possible interactions between management factors, although Smith et al . (1996a) demonstrated that such interactions were unimportant compared with the single effects of fertilizer, hay cut date and grazing treatments in a 4‐year field experiment on a traditional northern meadow in Upper Teesdale, northern England.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of such a temporally deep understanding is illustrated when considered alongside current ecological research into hay meadow management. While much is being gleaned from scientific field trials, authors such as Smith et al (1996) have suggested that it may take between 10 and 20 years for conclusive results to be gained on the exact impact of certain management schemes on meadow diversity. Oral histories, therefore, are uniquely placed to illustrate and understand longer-term impacts of particular managements -projecting back in time to link the current status of meadows to very specific past events and practices.…”
mentioning
confidence: 99%